Development of technical and economic means of increasing the efficiency of use of production resources for construction (for example, material and labor resources) - Oliferuk, S. (Ways to Improve Construction Efficiency, 2019)
Construction is a resource-intensive and labor-intensive activity, with significant cost savings and significant cost reductions in the case of increasing the efficiency of production resources in the construction process, optimization of the quality control system based on the principles of controlling and the development of appropriate technical and economic tools. The purpose of the study is to develop the feasibility of improving the efficiency of production resources by analyzing the cost structure of the estimated cost of construction and identifying adequate measures from the set of all possible sources of savings. The article provides a technical and economic analysis of the cost of production resources for construction work (BR), substantiates the "benchmark" from the standpoint of production efficiency of the structure of the cost of resources with the appropriate diagram, and also develops a scheme of choice of measures aimed at the rational use of necessary resources. Two variants of the structure of costs are analyzed, namely: the normative estimate and the actual structure of current costs of production resources for construction work The reason for the actual deviations in the main items of expenses was the decrease in the cost of using labor capital as a special type of production resources, which ensures economical and rational use of all other production resources (financial, material, energy, etc.). To improve the efficiency of production resources, it is necessary to provide planning and implementation of specific innovative measures for cost analysis and control, optimization of stocks, staffing with a stable composition of workers of the required professions, reducing the time for transportation, etc. Their careful implementation will significantly improve the economic structure of cost, bringing cost proposals to the "ideal" option.